Who owes? Class struggle, inequality and the political economy of leverage in the twenty-first century - Stefano Sgambati (Finance and Society, 2022)
The prevalent consensus in critical social sciences is that finance articulates the world economy as a global hierarchy of creditor-debtor relations that reproduce and further aggravate existing income and wealth inequalities. Class struggle is correspondingly understood as a conflict between elite creditors, who are members of the global top 1% of wealth holders, and mass debtors, who are burdened by growing costs of servicing public and private debts. This article offers an alternative understanding of how debt, inequality and class relate to one another. At its basis is the recognition that over the past four decades, finance has empowered upper class borrowers, including the top 1%, as it has magnified their capacity to generate capital gains and capture greater wealth and income shares via levered-up investments and other forms of positioning in financial and property markets. The article thus provides a political economy of leverage as power, showing how contemporary global finance has not given shape to a distributional conflict between creditors and debtors as two distinct classes, but instead has set debtors against debtors, and namely the greater borrowers against the lesser ones.
Keywords: 300; Class struggle; debt; finance; inequality; leverage; power